Efektivitas Kebun Buah Cepoko sebagai Media Diseminasi Informasi Pengembangan Tanaman Hortikultura di Kota Semarang - Juniarti, Hafni Amalia; Suwarto, Suwarto; Wijianto, Arip (Universitas Sebelas Maret, 2021)
Kebun Buah Cepoko is one of the work units farm owned by Unit Pelaksana Teknis Daerah (UPTD)/ Regional Technical Implementation Unit, Departement Agriculture of Semarang City Goverment. The success of farm optimization programs for the development of food crops and horticulture needs to be analyzed in effectiveness dissemination information at the development of horticultural. The purpose of the research was to (1) analyze the effectiveness of Kebun Buah Cepoko as a media dissemination information on horticultural development; (2) analyze the correlation between the level of education, frequency of communication, value economic benefits of commodities, level of cosmopolitan and agricultural information needs with the effectiveness of media dissemination of information on horticultural development; (3) analyze the comparative effectiveness of information dissemination media from the different farmer groups. This research used quantitative methods with questionnaires and interview techniques. The population was 32 horticultural farmers who visited the Kebun Buah Cepoko and received information on the development of horticultural in the December 2019 period. The sampling technique used total sampling with a total of 32 respondents. Data analysis used descriptive statistics analysis, Spearman Rank correlation analysis and Kruskal Wallis comparative analysis. The research showed that the effectiveness of Kebun Buah Cepoko as dissemination media for horticultural development information was 68.78% or in the average category. There was no significant correlation between the factors, farmers, accessing information, consisting of the level of education, frequency of communication, the value of economic benefits of commodities, cosmopolitan level and the need for agricultural information with the effectiveness of dissemination media information on horticultural plant development in Semarang City. The significance value correlation between the economic benefits of commodities with the effectiveness of dissemination media information on horticultural plant development was 0.062. There was a significant comparation of the effectiveness of dissemination media information between farmer groups. Asymp value was obtained sig 0.045.